The Archive of the University Library of Cagliari: formation, organisation and structure of administrative correspondence (1870-1955) - Andrea Pergola (Bibliothecae.it, 2023)
The Biblioteca Universitaria di Cagliari archive, formerly the subject of census activities, is now only partially ordered and lacking in finding aids. By examining the regulations that affected the Library from its promotion (1764) to the adoption of the Regulations for Government Public Libraries (1885), examining the administrative correspondence (1870-1955) and studying the classification and preservation practices adopted during the 19th century, this paper aims to contribute to the study of the archival history of the institution in order to foster future activities of reorganization and description of the Library’s documentary heritage.